THE INVOLVEMENT OF INJURIES IN ATHLETES AT THE CITY OF FORTALEZA (Fiep Bulletin - online, 2013)
His purpose of this article is to analyze the involvement of injuries in athletes at the city of Fortaleza, but also report on several, some factors that promote. The method used was the analytical, quantitative research through field research, with application of a structured questionnaire containing 13 questions. The results suggest that the main lesions found in the practice of capoeira are knee injuries 17.39%, and in the column, also with 17.39%, having multiple lesions reached the index of 30.43% of cases reported in this study. The main causes of injury are: the mechanics, like the quick shifts, repetitive and exhausting and sudden changes of direction (which accentuate the action of the force of friction and consequently the ground reaction force); and biological as the muscular system weakened, the proprioceptive action fails and the limited muscle flexibility, in addition to the location of the practice, which is often unsuitable for this type of activity.
Keywords: Injury; Capoeira; Prevention; Treatment